Ecotheological Leadership in Responding to the Environmental Crisis in Islamic Educational Institutions - Undiadi Undiadi; Nanda Zahratu Raudah; S. Ali Jadid Alaydrus; Maimun Maimun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
The accelerating environmental the accelerating environmental crisis including ecological degradation, climate change, and the depletion of natural resources poses serious challenges for educational institutions, particularly those carrying moral and spiritual responsibilities such as Islamic schools and madrasahs. This study explores how ecotheological leadership functions as an integrative ethical and managerial paradigm in responding to environmental challenges within Islamic educational institutions through leadership quality management practices. The primary issue addressed is the insufficient integration of ecological values into leadership management models that often emphasize administrative performance while neglecting environmental responsibility and spiritual ethics. Employing a qualitative descriptive approach supported by literature review, in-depth interviews, observations, and document analysis, this research investigates leadership practices grounded in Islamic ecotheological principles, including khalīfat al-arḍ (stewardship of the earth), amānah (trust), and maṣlaḥah (public good). The findings demonstrate that ecotheological leadership plays a crucial role in institutionalizing ecological ethics through participatory governance, curriculum integration, environmentally oriented policies, and accountability mechanisms within quality management systems. These approaches foster sustainability awareness among educators and students while strengthening institutional culture and responsibility. The study concludes that ecotheological leadership provides a transformative leadership model in which environmental stewardship becomes an essential component of educational governance rather than a peripheral initiative, aligning Islamic moral theology with sustainable development goals to ensure educational quality and ecological sustainability for present and future generations